Phase Transitions in Solids Under High Pressure. - Blank, Vladimir Davydovich (Taylor and Francis, 2013)
The use of high-pressure techniques has become popular for studying the nature of substances and phenomena occurring in them, especially as a means of obtaining new materials (synthesis under high pressure) and processing known materials (hydroextrusion). A product of many years of research by the authors and their colleagues, Phase Transitions in Solids under High Pressure discusses the relationships of phase transformations in solids under high pressure, the mechanism of these transformations, crystal geometry, the effect of deformation, the conditions of formation, and preservatio.